Analysis of the Causes of Deviations in the Implementation of Construction Work Contracts Based on Verdict - ‘Ainaqi, Qorri; Ophiyandri, Taufika; Hidayat, Benny (CIVED, 2024)
Construction Work is the whole or part of the activities that include the construction, operation, maintenance, demolition, and rebuilding that are regulated in a Construction Contract. In the implementation of the Construction Contract, several problems cause deviations. The purpose of this research is to analyze the causes of deviations in a Construction Contract based on Verdict. The research data was obtained from the Supreme Court Repository page by searching for Verdict related to implementing Construction Contracts. The limitation of this research is a case that has been decided in the last 10 years in the District Court in West Sumatra. The search results obtained 9 verdicts. The method used to analyze the data is the Rich Picture Diagram (RPD). Validation and refinement are carried out using the Interview method from the results of secondary data analysis. The outcome of this research is the causes of deviations that are prejudicial to one of the parties and thus fall under civil law such as The occurrence of delays caused by: Contractor negligence during implementation, Contractor achievements not paid by the Owner, negligence of the Planner Consultant, the state of the land is not by the drawing plan, continuous heavy rain that disrupts the work, Kurs strengthen sharply, land acquisition has not been completed by the Owner, the Contractor is not given the opportunity 50 days of completion; Disputes caused by: Owner made unilateral changes to Technical Specifications, Supervisory Consultant's mistake in reporting progress.